2012
DOI: 10.1111/j.1466-7657.2012.01011.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric readmission: an integrative review of the literature

Abstract: It was noted that the perspective of the patient regarding their readmissions, as well as the interface with the social and familial context in which they maintain their social relationships and care for their health, was largely unexplored by the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 23 publications
2
24
0
8
Order By: Relevance
“…The review strategy involved the following steps:15,16 1) carry out a systematic survey of national and international publications on ED, social networks, and social support; 2) identify the authors, types of studies, years of publication, journals in which these studies were published, the origin of the articles, which language they were written in, the goals of the study, and the obtained results; and 3) conduct a descriptive analysis of the studies’ findings and provide a critical evaluation of the contributions offered for the production of knowledge on the subject.…”
Section: Methodsmentioning
confidence: 99%
“…The review strategy involved the following steps:15,16 1) carry out a systematic survey of national and international publications on ED, social networks, and social support; 2) identify the authors, types of studies, years of publication, journals in which these studies were published, the origin of the articles, which language they were written in, the goals of the study, and the obtained results; and 3) conduct a descriptive analysis of the studies’ findings and provide a critical evaluation of the contributions offered for the production of knowledge on the subject.…”
Section: Methodsmentioning
confidence: 99%
“…Atualmente, as políticas em saúde mental do Estado brasileiro se caracterizam por ações integradas dos governos federal, estadual, municipal e de movimentos sociais, que buscam efetivar a pretendida transição do modelo centrado no hospital psiquiátrico para um modelo de atenção comunitário e baseado na comunidade (Machado, Leonidas, & Santos, 2012). Esse novo modelo é chamado Atenção Psicossocial (Amarante, 2011;Costa-Rosa, 2000) ou Estratégia Atenção Psicossocial (Costa-Rosa, 2013;Yasui & Costa-Rosa, 2008), que não se restringe à disponibilização de uma rede de serviços que se propõem a substituir o manicômio, mas representa a instauração de um outro paradigma de cuidado em saúde mental, que acompanha a mudança paradigmática implantada em diversos países e continentes envolvendo desde a problematização do conceito de saúde mental até as táticas de tratamento e as estratégias de cuidado (Yasui, 2010).…”
Section: Novos Ventos Chegam Aos Trópicos: a Reforma Psiquiátrica Braunclassified
“…Repeated hospitalisations for patients with psychiatric disorders may reflect the type of illness, but also environmental factors and underlying inefficiencies in pre- and post-discharge treatment [1]. Readmissions may be disruptive to patients and their families, and represent a strain on limited health care resources.…”
Section: Introductionmentioning
confidence: 99%
“…Also, previous reviews have typically identified and discussed system characteristics as pre- or post-discharge service use of psychiatric patients [1, 7, 8]. However, in many instances there is not a clear cut separation between patient characteristics and systems characteristics.…”
Section: Introductionmentioning
confidence: 99%